Chronology and climate sensitivity of the post‐LGM glaciation in the Dunagiri valley, Dhauliganga basin, Central Himalaya, India. (24th April 2020) - Kumar, Vinit; Shukla, Tanuj; Mishra, Ajai; Kumar, Anil; Mehta, Manish
Abstract : In this study, we reconstruct the style and timing of the late Quaternary glaciation pattern in a monsoon‐influenced precipitation‐deprived region (Dhauliganga basin) of the Central Himalaya, India. We present detailed glacial geomorphological mapping, aided by topographic maps, satellite data, Google Earth images, global positioning system survey, and fieldwork (2012–2016), supported by optically stimulated luminescence dating. Our estimations for the magnitude and timing of glaciations in the Dunagiri Glacier valley suggest five sets of glacial advances. The oldest and most extensive glaciation in the valley is Dunagiri Glacial Stage‐I (DGS‐I), represented by a discontinuous moraine ridge that extends down to ~10 km (~2700 m a.s.l.) from the present‐day snout and formed 13±3 ka ago. The DGS‐II stage is present in the form of a small moraine ridge (~3000 m a.s.l.) that formed 10±2 ka ago. The DGS‐III and DGS‐IV glacial stages are 5 – 6 and 3.5 ka old, respectively. The youngest stage (DGS‐V) of glaciation belongs to the neoglaciation episode ~1 ka old. DGS‐I was the most extensive glaciation in the valley and corresponds to the global Last Glacial Maximum. The glaciation pattern has been correlated with the estimates of present‐day glacial sensitivity to climate and explained as forcing factors sensitive to temperature and/or precipitation changes in the region. The observations based on prevailing climate correlations aided with available glacial chronologies underline the fact that the glacial valleys situated in precipitation‐deprived regions have preserved a delayed response of glaciations to regional climatic events. Estimates for the timing and pattern of glaciation in the present study suggest a different glacial response for modern climatic changes than previously assumed. We suggest that individual glacier advances differ regionally and, therefore, should not be interpreted as being reflective of a change in the whole geographical belt.